2014
DOI: 10.1016/j.optcom.2014.06.048
|View full text |Cite
|
Sign up to set email alerts
|

Quantum estimation of magnetic-field gradient using W-state

Abstract: We study the precision limits of detecting a linear magnetic-field gradient by using W-states in the presence of different types of noises. We consider to use an atomic spin chain for probing the magnetic-field gradient, where a W-state is prepared. We compare this method with the measurement of using two uncorrelated atoms. For pure states, W-states can provide an improvement over uncorrelated states in determining the magnetic-field gradient up to four particles. We examine the effects of local dephasing and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Instead, the parameter(s) of interest could be some function(s) of φ, e.g., k φ k . In this case, the aim is to optimize the QSN for estimating these functions, and this encompasses many important problems, including measuring: phase differences in one [49] or more [14] interferometers; the average or sum of many parameters [17]; a linear gradient [50,51]. A global property of the network is some vector (or scalar) with elements that are functions of {φ k } depending non-trivially on many or all of the φ k , which includes the examples given above.…”
Section: R(ϕ) ≤ R(ρ)mentioning
confidence: 99%
“…Instead, the parameter(s) of interest could be some function(s) of φ, e.g., k φ k . In this case, the aim is to optimize the QSN for estimating these functions, and this encompasses many important problems, including measuring: phase differences in one [49] or more [14] interferometers; the average or sum of many parameters [17]; a linear gradient [50,51]. A global property of the network is some vector (or scalar) with elements that are functions of {φ k } depending non-trivially on many or all of the φ k , which includes the examples given above.…”
Section: R(ϕ) ≤ R(ρ)mentioning
confidence: 99%
“…C is function of gradient G and can easily be experimentally measured [23], i.e., after first time measurement (making NV − a and NV − b entangled) on the quantity of C , we can derive gradient G x , then the second round trial (making NV − a and NV − c entangled) will figure out the value of G y . Fig.…”
Section: Detection Of Magnetic-field Gradientmentioning
confidence: 99%
“…Observe the phase transition at the point where the parameters are equal. Substituting equations (20) and (28) into equation (10) and performing the integration over s yields ( ) where we have again separated the linear and oscillatory parts in t. As equation (29) is of the same form as equation (16) it can be brought to the diagonal form…”
Section: Estimating the Field Strengthmentioning
confidence: 99%
“…In stark contrast quantum metrology with more general Hamiltonians is only now beginning to attract attention. Some instances of quantum metrology with parameter dependent Hamiltonians concern the estimation of time-varying signals [24][25][26], the estimation of magnetic-field gradients along a spin chain [27][28][29], or the estimation of the anisotropy and/or decoherence along a spin-chain using non-equilibrium states [30]. The general problem of performing quantum metrology using parameter dependent Hamiltonians was treated in [31,32] where it was shown that for parameter dependent local Hamiltonians Heisenberg scaling precision with respect to the number of probing systems is possible.…”
Section: Introductionmentioning
confidence: 99%